Living a feminist life - Ahmed, Sara (Duke University Press, 2017)
In Living a Feminist Life Sara Ahmed shows how feminist theory is generated from everyday life and the ordinary experiences of being a feminist at home and at work. Building on legacies of feminist of color scholarship in particular, Ahmed offers a poetic and personal meditation on how feminists become estranged from worlds they critique-often by naming and calling attention to problems-and how feminists learn about worlds from their efforts to transform them. Ahmed also provides her most sustained commentary on the figure of the feminist killjoy introduced in her earlier work while showing how feminists create inventive solutions-such as forming support systems-to survive the shattering experiences of facing the walls of racism and sexism. The killjoy survival kit and killjoy manifesto, with which the book concludes, supply practical tools for how to live a feminist life, thereby strengthening the ties between the inventive creation of feminist theory and living a life that sustains it. https://www.saranahmed.com/
Keywords: 2000 à aujourd'hui; 2010-2019; afrique; afro-féminisme; approches et analyses; care; corps; cours; discipline; fem1000; féminismes noirs; incontournable; intersectionnalité; manifeste; militance; occident; orient; philosophie; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; émotions; études culturelles

Plaisirs croisés: gukuna-kunyaza. Missions, corps et sexualités dans le Rwanda contemporain - Michela Fusaschi (Genre, Sexualité et Société, 2012)
Based on ethnographic research in post-genocide Rwanda, this article analyzes how femininity is embodied through a ritual practice called gukuna, which consists of the elongation of the labia minora through a reciprocal massage between young women. This social construction of the female body, in addition to kunyaza, a traditional male sexual technique, is expected to facilitate pleasure during sexual intercourse. Through an analysis of colonial period texts as well as recent interviews, this article shows how this ritual, has persisted in the country despite its condemnation by the Catholic Church since the colonial time, and explores how it is being reinterpreted by women.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; afrique; afro-féminisme; approches et analyses; corps; cours; discipline; féminisme africain; gukuna; premier cycle; périodes historiques; rituel; rwanda; régions géographiques; science politique; science politique et droit; sex2283; sexualité; thématiques

Métissage, l’histoire en héritage - Binge Audio
Grace Ly et Rokhaya Diallo discutent de la complexité du mot “métis” –expression dont l’histoire est lourde des violences coloniales. Avec Jessica Gérondal Mwiza, franco-rwandaise et autrice du billet de blog « Je ne suis pas métisse, je suis une femme noire » sur Médiapart, elles remettent en question ce terme qui s’inscrit d’abord dans une vision biologique de la race, et que certains érigent en horizon utopique de l’humanité quand d’autres en font une catastrophe annoncée. Difficile à porter pour les principaux.ales concerné.e.s, dont l’expérience raciale est bien particulière, entre fascination, exotisation, colorisme, et racisme.
Keywords: afrique; afro-féminisme; approches et analyses; colorisme; corps; cours; europe; exotisation; fem3300; france; féminisme africain; féminismes noirs; histoire et politique; premier cycle; racisme; ressource en ligne; rwanda; régions géographiques; sexisme; système colonial; systèmes d'oppressions; thématiques; violences